Paradise Lost - Paradise Regained : American Visions of the New Decade : La 41a Biennale di Venezia 1984 - United States Pavilion. - Gumpert, Lynn; Rifkin, Ned; Tucker, Marcia; 41e Biennale di Venezia, 1984 - pav. Amerika (New York : The New Museum of Contemporary Art, 1984)
Bosman, Richard ; Brown, Roger ; Chase, Louisa ; Cooling, Janet ; Dean, Peter ; Finster, Reverend Howard ; Fischl, Eric ; Garabedian, Charles ; Garet, Jedd ; Gornik, April ; Green, George Thurman ; Kassel, Barbara ; Laemmle, Cheryl ; Levers, Robert ; Linhares, Judith ; Mendelsohn, John ; Miller, Melissa ; Morosan, Ronald ; Smith III, Lee N. ; Staley, Earl ; True, David ; Warren, Russ ; Wong, Tony ; Yarber, Robert
biografie, bibliografie
41e Biennale di Venezia, 1984 - United States Pavilion, 10.06 - 09.09.1984
Italiaans & Engels
kunstcatalogus
Keywords: Amerika